2017
DOI: 10.1007/s10584-017-1923-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating wildfire response costs in Alaska’s changing climate

Abstract: Climate change is altering wildfire activity across Alaska, with increased area burned projected for the future. Changes in wildfire are expected to affect the need for management and suppression resources; however, the potential economic implications of these needs have not been evaluated. We projected area burned and associated response costs to 2100 under relatively high and low climate forcing scenarios (representative concentration pathways (RCP) 8.5 and 4.5) using the Alaskan Frame-based Ecosystem Code (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Climate change is altering wildfire activity across Alaska, with an increase in the burned area projected for the future. The cumulative area burned predicted between 2006 and 2100 across Alaska averaged 46.7 M ha under five climate models for RCP8.5 and 42.1 M ha for RCP4.5, with estimated cumulative response costs of $1.2-2.1 B and $1.1-2.0 B, respectively (3% discount) [24]. Yue et al found that for Alaska and western Canada, almost all models predict significant (p < 0.05) increases in the area burned at mid-century (2046-2065) under the A1B scenario, with median values ranging from 150% to 390% depending on the ecoregion [25].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is altering wildfire activity across Alaska, with an increase in the burned area projected for the future. The cumulative area burned predicted between 2006 and 2100 across Alaska averaged 46.7 M ha under five climate models for RCP8.5 and 42.1 M ha for RCP4.5, with estimated cumulative response costs of $1.2-2.1 B and $1.1-2.0 B, respectively (3% discount) [24]. Yue et al found that for Alaska and western Canada, almost all models predict significant (p < 0.05) increases in the area burned at mid-century (2046-2065) under the A1B scenario, with median values ranging from 150% to 390% depending on the ecoregion [25].…”
Section: Introductionmentioning
confidence: 99%
“…2014 ). Finally, though projections of climate change impacts on wildfires in Alaska demonstrate significant increases in the number of acres burned, particularly under RCP8.5 ( Melvin et al. 2017 ), this study could not include Alaska exposure estimates as the LOCA downscaling was only available for the contiguous United States.…”
Section: Discussionmentioning
confidence: 99%
“…Climate projections for Alaska have predicted increases in statewide average annual fire frequency, area burned, and fire season length during the first half of the 21st century (Mann et al 2012, Rupp et al 2016. These projected future increases in fire activity will likely exacerbate the costs of fire management or, alternatively, leave managers in a position where they are no longer able to maintain fire management activities at current levels (Melvin et al 2017).…”
Section: Adaptive Governance For Fire In Alaskamentioning
confidence: 99%
“…Climate change projections show that the number of days that support fire intensities that exceed suppression capabilities will become more frequent in the boreal forest, rendering suppression infeasible at times, regardless of the availability of suppression resources (Wotton et al 2017). Recent literature has shown that creating breaks in the most flammable boreal fuel types can aid suppression and reduce risk to valued resources; consequently, the use of fuel management by both Alaska's land and fire management agencies has grown (Beverly 2017, Melvin et al 2018. Fuel reduction treatments, however, do not effectively change area burned or reduce the occurrence of higher intensity fires when assessed at large spatial extents (Cary et al 2017).…”
Section: Adaptive Governance For Fire In Alaskamentioning
confidence: 99%